KETERBATASAN TEKNOLOGI DALAM PRODUKSI TEMPE DAN TAHU: (TANTANGAN AGROINDUSTRI DI KAWASAN TIMUR INDONESIA) - Krisna Fransina Lermating; Sri Anggasari Makatita; Hendry Jems Yoel Aidore (Jurnal Administrasi Terapan, 2025)
Limited access to modern technology remains a major challenge in the development of tempeh and tofu agroindustry in Eastern Indonesia, particularly in South Sorong Regency. Most processing businesses in the region still rely on traditional equipment and manual methods, resulting in low productivity, inconsistent product quality, and limited production capacity. This study aims to analyze the impact of technological limitations on business efficiency and the sustainability of tempeh and tofu production. A descriptive qualitative method was used with a case study approach involving five small-scale enterprises in South Sorong Regency. Data were collected through direct observation and interviews with business owners. The findings show that all respondents still use basic tools such as wood-fired stoves, plastic containers, and natural fermentation materials. The absence of appropriate technology leads to time-consuming processes, high operational costs, and short product shelf life. Additionally, the lack of training and government support further hinders business development. Therefore, technological intervention, production management training, and policy support are needed to improve the efficiency and competitiveness of tempeh and tofu agroindustry in Eastern Indonesia. Keywords: technology; agroindustry; tempeh; tofu; Papua